Fragility functions for fiber-reinforced polymers strengthened reinforced concrete beam-column joints - Yurdakul, Özgür; Del Vecchio, Ciro; Di Ludovico, Marco; Avsar, Ozgur; Prota, Andrea (Elsevier Science, 2023)
Post-earthquake field inspections have outlined the poor seismic performance of non-conforming reinforced concrete (RC) beam-column joints (BCJs) of existing RC buildings. Experimental and analytical studies have demonstrated that the application of externally bonded fiber-reinforced polymers (FRPs) is an efficient and cost-effective strengthening technique to improve the seismic performance of deficient BCJs. However, seismic losses for FRP-strengthened BCJs at different damage states (DSs) are currently not quantified. A potential seismic damage assessment tool is critical to obtain reliable estimations of the effects of FRP strengthening on reducing the expected damage and losses in existing buildings. Therefore, experimental-based fragility functions for FRP-strengthened corner and exterior BCJs at different limit states are proposed in this study. Experimental tests on 70 corner and 28 exterior FRP-strengthened BCJs are first collected. Then, DSs with increasing severity (i.e., light, moderate, and heavy) are defined according to widely recognized studies. These DSs are quantified on the basis of inter-story drift ratios (IDRs). After retrofitting, IDR-based fragility functions are generated for strengthened BCJs classified in terms of failure mode and achieved ductility level. The proposed functions are also compared with fragility functions available for non-conforming and conforming joints obtained from the literature. Finally, an application of the proposed fragility functions within a performance-based earthquake engineering (PBEE) framework for quantifying expected losses (ELs) and the benefits of FRP strengthening of BCJs is showed.
Fragility functions for fiber-reinforced polymers strengthened reinforced concrete beam-column joints
Keywords: FRP; Expected Annual Losses; Seismic retrofit; Composite materials; PBEE; FRP; Expected Annual Losses; Seismic retrofit; Composite materials; PBEE